Destiny of the dead - Kade, Kel (Shroud of prophecy series, 2022)
"Destiny of the Dead is the second novel in a genre-bending series from New York Times bestselling author Kel Kade. The God of Death is tired of dealing with the living, so he's decided everyone should die. And he's found allies. The Berru, an empire of dark mages, has unleashed a terrifying army of monstrous lyksvight upon everyone with a pulse. While the wealthy and powerful, the kings and queens, abandon the dying world, one group of misfits says no more. Through dogged determination and the ability to bind souls to their dead bodies, Aaslo and his friends fight on. In the mountains of the far north, another bastion of defense is opened. Cherrí, the avatar of a vengeful fire god, has united the survivors amongst her people and begun her own war on the invaders. Now, Aaslo and Cherrí must find a way to unite their powers, one divine, the other profane, to throw back the monsters of the Berru, and challenge Death itself"--